Digital Development: Elements of a Critical ICT4D Theory and Praxis - Bon, Anna; Akkermans, Hans (Springer International Publishing, 2019)
In recent years, critical research literature in ICT4D has grown. It i s widely accepted that theory is to inform practice. However, the inve rse directionality, practice informs theory, is much less present in I CT4D, including in critical research. In this paper, we discuss ways h ow ICT4D research and theory may be better informed by practice—in ter ms of (i) recognizing praxis-oriented research paradigms and integrati ng their results, (ii) development of foundational theories, (iii) cri tical analysis of ICT4D emerging policies, and (iv) positioning ICT4D in the wider development debate. This suggests several elements or dir ections in which critical research has the potential to push current b oundaries of ICT4D in terms of content as well as relevance.
Keywords: Action research paradigm; Critical research; Network complexity theory; Principles for Digital Development